Alexithymia and Emotional Deficits Related to Posttraumatic Stress Disorder: An Investigation of Content and Process Disturbances - Ewa A. Ogłodek (Case Reports in Psychiatry)
Background. Posttraumatic stress disorder (PTSD) is a debilitating mental disorder that develops in the aftermath of traumatic life experiences, especially those that occurred in childhood. PTSD is associated with intrusive memories, distressing dreams, dissociative reactions, avoidance of trauma-related stimuli, negative mood and sense of well-being, increased arousal and irritability, and clinically significant distress and impaired functioning. Case Presentation. The following case report presents a 42-year-old male displaying symptoms of PTSD, alexithymia, and depression. Conclusion. Untreated alexithymia may aggravate the trauma and cause the development of PTSD and depression.